2011
DOI: 10.1016/j.gaitpost.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study about the relationship between morphology and kinematic parameters in children between 15 and 36 months

Abstract: Morphology and kinematic parameters were recorded for 31 children between 15 and 36 months to investigate the relation between morphology and the walking pattern. A full 3D gait analysis using a VICON motion system was performed to gather kinematic data. Next, the differences in kinematic parameters between four morphological classes were assigned with a multiple analysis of variance, with a correction for walking experience. Also stepwise linear regressions were performed, to examine the relation between deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Infants acquire new motor skills in a body that is continually changing. Developmental changes due to growth, redistribution of muscle and fat, changes in muscle strength and elasticity, and so on alter the constellation of forces at work (Van Dam et al 2011). Likewise, temporary changes to the body (due to clothing, footwear, backpacks, objects in hand, etc.)…”
Section: Motor Development Is Embodiedmentioning
confidence: 99%
“…Infants acquire new motor skills in a body that is continually changing. Developmental changes due to growth, redistribution of muscle and fat, changes in muscle strength and elasticity, and so on alter the constellation of forces at work (Van Dam et al 2011). Likewise, temporary changes to the body (due to clothing, footwear, backpacks, objects in hand, etc.)…”
Section: Motor Development Is Embodiedmentioning
confidence: 99%
“…Out of databases from previous studies all 3D gait analysis of typically developing children that met following inclusion criteria were selected: a total body gait analysis with clear foot strikes on the force plates and full marker visibility for at least two consecutive strides. Details of participant selection in the previous studies is dependent upon the study and can be found in previous publications [18][19][20][21][22].…”
Section: Participantsmentioning
confidence: 99%
“…Clothing, footwear and surfaces are likely to have an influence on the infant both in terms of mechanical and proprioceptive effects, but despite this these conditions are rarely reported in research studies ( Table 2). The body morphology of infants has also been shown to influence temporal-spatial (51) and kinematic characteristics of walking in toddlers, in particular maximum hip adduction in stance decreases in infants classed as 'slimmer' (52). The authors attributed these findings to lower inertia in the frontal plane of the thorax/head in more slim infants leading to less resistance against sideways movement.…”
Section: Whilst Infant Foot Kinematics During Gait Have Received Limimentioning
confidence: 99%